1995
DOI: 10.1128/aem.61.11.3815-3820.1995
|View full text |Cite
|
Sign up to set email alerts
|

Production of volatile sesquiterpenes by Fusarium sambucinum strains with different abilities to synthesize trichothecenes

Abstract: Twenty-five strains of Fusarium sambucinum grown on wheat kernels were examined for trichothecene production and the synthesis of volatile sesquiterpenes. The volatiles were purged with air and collected on Tenax traps. Adsorbed compounds were eluted from the traps and injected into a gas chromatograph coupled with a mass spectrometer. Ten strains isolated from potato tubers produced high amounts of diacetoxyscirpenol and its derivatives. These strains were characterized by the production of high amounts of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(25 citation statements)
references
References 18 publications
2
22
0
1
Order By: Relevance
“…They, as well as (El-Banna et al 1984), found that trichothecenes were formed in potato tubers infected with F. sambucinum. Jelen et al (1995) and Ellner (2002) detected A-type trichothecenes (e.g. DAS, MAS) in all potato tubers inoculated with F. sambucinum.…”
Section: Discussionmentioning
confidence: 95%
“…They, as well as (El-Banna et al 1984), found that trichothecenes were formed in potato tubers infected with F. sambucinum. Jelen et al (1995) and Ellner (2002) detected A-type trichothecenes (e.g. DAS, MAS) in all potato tubers inoculated with F. sambucinum.…”
Section: Discussionmentioning
confidence: 95%
“…3), while the other treatments showed no common associations throughout the measurements. The relatively high selinene emission may mainly have originated from the fungi present on the litter (Jelén et al, 1995;Jelén, 2002). By contrast, humulene may have been released from the mountain birch leaf litter itself, as living foliage emits humulene (Mäntylä et al, 2008).…”
Section: Bvoc Emission Associations Are Seasonal and Affected By Warmingmentioning
confidence: 99%
“…In addition to the nonvolatile mycotoxin metabolites, a wide spectrum of 50 volatile and 53 semivolatile metabolites (microbial volatile organic compounds [mVOC]) is also produced by different Fusarium species . An important class of semivolatile metabolites are the sesquiterpenes, which serve as building blocks in the biosynthesis of mycotoxins . Other fungi, encountered as field or storage pest alike, are various Alternaria, Aspergillus, and Penicillium species.…”
Section: Introductionmentioning
confidence: 99%